(untitled) (Texas Journal of Medical Science, 2022)
The purpose of the study: to determine methodological ways to improve the special performance of qualified boxers in the process of an individual lesson on the "paws". Materials and methods. The study and generalization of the experience of best practices was carried out with the help of a questionnaire survey and conversations with leading coaches and athletes of Uzbekistan and the Surkhandarya region. With the help of these methods, opinions were revealed on a number of theoretical, methodological and practical issues of individual learning. Accounting for the volume and intensity of training loads in the individual lessons of boxers on the “paws” in the process of sports training was carried out using video surveillance. The functional state of the boxers was assessed by the values of heart rate, fixed by means of "Polar H10 MXXL", before the load and after each individual type of load. To process the data and the results of the study, we used the SPSS Statistics program (“Statistical Package for the Social Sciences”), designed for applied research in the social and pedagogical sciences